1989
DOI: 10.1093/jnci/81.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of N-ras Oncogene and Epidermal Growth Factor Receptor Gene in Human Glioblastomas

Abstract: Five human glioblastoma cell lines were analyzed for oncogene activation with a panel of probes. Abnormal expression of the epidermal growth factor receptor (EGFr) gene was detected in four of five lines; N-ras oncogene overexpression was found in all five cell lines. These results were subsequently confirmed with fresh brain tumor and nonneoplastic brain tissue biopsy samples; increased expression of the N-ras proto-oncogene was observed in five of five glioblastomas, all of which also showed EGFr gene overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 0 publications
2
21
0
1
Order By: Relevance
“…Elevated levels of c-erbB-l mRNA occurred independently of amplification in 17 of 19 (89%) gliomas in one study (Malden et al, 1988). Activation, characterised by elevated mRNA levels, of c-myc (Englehard et al, 1989;Trent et al, 1986), N-myc (Garson et al, 1985;Kinzler et al, 1986;Fujimoto et al, 1989), N-ras (Gerosa et al, 1988) and gli has also been reported in glial tumours.…”
Section: Discussionmentioning
confidence: 90%
“…Elevated levels of c-erbB-l mRNA occurred independently of amplification in 17 of 19 (89%) gliomas in one study (Malden et al, 1988). Activation, characterised by elevated mRNA levels, of c-myc (Englehard et al, 1989;Trent et al, 1986), N-myc (Garson et al, 1985;Kinzler et al, 1986;Fujimoto et al, 1989), N-ras (Gerosa et al, 1988) and gli has also been reported in glial tumours.…”
Section: Discussionmentioning
confidence: 90%
“…Alternatively, if astrocytomas progress from low to higher grades (James et al, 1988), they may do so by step-wise changes in the p53 gene, analogous to those proposed for colorectal carcinomas: the first or initiating step involving mutation in one allele only and a synthesis of inactive mutant/normal oligomers; further loss of control is believed to result from deletion of the normal allele, leaving the cell with only a mutant allele (Liberman et al, 1984; and immunohistochemical studies on astrocytomas (Reifenberger et al, 1989), and extend them by survival data. But, unlike human breast cancer (Shimizu et al, 1985), or to loss of control of transcriptional activity of the gene (Gerosa et al, 1989 (Bigner et al, 1984;Shapiro, 1986;James et al, 1988). In model for progression of gliomas Bigner and Vogelstein (1990) …”
Section: Discussionmentioning
confidence: 99%
“…However, in spite of accumulating knowledge of the expression and function of the N-ras gene, information about its transcriptional regulation is still limited. Although the most commonly reported tumor-associated lesion of ras is a point mutation which generates an oncogenic (activated) protein (Barbacid, 1987), ras overexpression has also been implicated in the generation of human tumors (Gerosa et al, 1989) and tumor-derived cell lines (Doniger and DiPaolo, 1988). This indicates that careful regulation of the N-ras gene may be crucial for prevention of oncogenic transformation.…”
Section: Introductionmentioning
confidence: 99%